M19 Patient perspectives of an ambulatory pleural service. (15th November 2016) - Devani, N; Gupta, U; Kaiser, R; Johns, RH
Abstract : Background and objectives: Barking, Havering and Redbridge University Trust (BHRUT) serves a population of 750, 000 patients with a large burden of pleural disease. Patients admitted and requiring pleural drainage usually results in a long length of stay of around 7–10 days. Outpatient ambulatory management of undiagnosed and known malignant pleural effusions is increasing nationally in the UK through development of pleural clinics. Previous reports have demonstrated these to be financially efficacious and avoid hospitalisation. We sought to demonstrate that they are also well received and favoured by patients. Methods: In December 2015, an outpatient weekly pleural aspiration service was established receiving referrals directly from respiratory outpatients, A&E and acute medicine. We prospectively audited patients attending this service between December 2015 and June 2016. Patients were asked to complete an in-depth questionnaire to assess their experience on the day, any procedural discomfort and attitudes toward such an outpatient service. Results: 81 patients attended our service over this period. Median age was 74 (range 30–92), 40% female. 58 patients returned a completed questionnaire. 86% of patients were seen within a week of referral with the rest waiting less than 2 weeks. The majority (74%, n = 43) of patients did not notice any deterioration in their symptoms during this wait. Median pain score was 3(range 1–10). 78% (n = 45) of patients felt they could continue with their normal activities post procedure. Only 2 patients would have preferred to undergo the procedure as an inpatient citing frailty as the reason. 98% (n = 57) of patients felt that an outpatient pleural service was a good idea. 78% (n = 45) rated the service as excellent, 17% (n = 10) as 'above average' and only 5% (n = 3) as 'average.' Conclusions: Outpatient management of pleural effusions is favoured by patients with most rating our service as excellent. Patients are seen promptly with the majority reporting no deterioration in their symptoms during the wait. The procedure is well tolerated and allows patients to continue with their normal daily activities. In addition to important financial benefits of reducing hospital bed-days in patients with pleural effusions, our newly established service has been shown to be beneficial in promoting a positive patient experience.